The complete genome sequence of Bacillus halotolerans ZB201702 isolated from a drought- and salt-stressed rhizosphere soil. (October 2018) - Zhang, Zhongbao; Yin, Longfei; Li, Xianglong; Zhang, Chun; Liu, Cai; Wu, Zhongyi
Abstract: Bacillus halotolerans is a rhizobacterium with the potential to promote plant growth and tolerance to drought and salinity stress. Here, we present the complete genome sequence of B . halotolerans ZB201702, which consists of 4, 150, 000 bp in a linear chromosome, including 3074 protein-coding sequences, 30 rRNAs, and 85 tRNAs. Genome analysis revealed many putative gene clusters involved in defense mechanisms. Activity analysis of the strain under salt and simulated drought stress suggests tolerance to abiotic stresses. The complete genome information of B . halotolerans ZB201702 could provide valuable insights into rhizobacteria-mediated plant salt and drought tolerance and rhizobacteria-based solutions for abiotic stress agriculture. Highlights: Present the complete genome sequence of B. halotolerans ZB201702 with no gap. Genome analysis revealed many putative gene clusters involved in defense mechanisms. The strain can resist salt and simulated drought stress.